FAUST I. The hot corino at the heart of the prototypical Class I protostar L1551 IRS5. (21st July 2020) - Bianchi, E; Chandler, C J; Ceccarelli, C; Codella, C; Sakai, N; López-Sepulcre, A; Maud, L T; Moellenbrock, G; Svoboda, B; Watanabe, Y; Sakai, T; Ménard, F; et al.
ABSTRACT: The study of hot corinos in solar-like protostars has been so far mostly limited to the Class 0 phase, hampering our understanding of their origin and evolution. In addition, recent evidence suggests that planet formation starts already during Class I phase, which therefore represents a crucial step in the future planetary system chemical composition. Hence, the study of hot corinos in Class I protostars has become of paramount importance. Here, we report the discovery of a hot corino towards the prototypical Class I protostar L1551 IRS5, obtained within the ALMA (Atacama Large Millimeter/submillimeter Array) Large Program FAUST (Fifty AU STudy of the chemistry in the disc/envelope system of solar-like protostars). We detected several lines from methanol and its isotopologues ( 13 CH3 OH and CH2 DOH), methyl formate, and ethanol. Lines are bright towards the north component of the IRS5 binary system, and a possible second hot corino may be associated with the south component. The methanol lines' non-LTE analysis constrains the gas temperature (∼100 K), density (≥1.5 × 10 8 cm −3 ), and emitting size (∼10 au in radius). All CH3 OH and 13 CH3 OH lines are optically thick, preventing a reliable measure of the deuteration. The methyl formate and ethanol relative abundances are compatible with those measured in Class 0 hot corinos. Thus, based on this work, little chemical evolution from Class 0 to I hot corinos occurs.